Enhancing Internship Assignment Efficiency Through Spreadsheet-Based Linear Programming - Ahmad Hudawi; Matlubul Khairi; Ach Ramadhani (JOKI: Jurnal Komputasi dan Informatika, 2025)
Internship programs serve as a vital bridge between academic knowledge and real-world practice, preparing students for professional environments. However, the manual process of assigning students to internship positions often results in inefficiencies, misalignments between student skills and job roles, and unnecessary costs. This study introduces a spreadsheet-based linear programming approach using Microsoft Excel Solver to optimize the assignment of internship students to tasks, aiming to minimize total costs while maximizing task compatibility. The model incorporates student profiles, task-specific skill requirements, and associated costs to generate the most efficient allocation. Results show that all four students in the case study were optimally assigned to distinct tasks coding, UI/UX design, editing, and data analysis at the lowest total operational cost of IDR 277,000. The proposed method not only ensures task relevance for each intern but also significantly improves the assignment efficiency. These findings suggest that Excel Solver can be a practical and accessible decision-support tool for academic institutions and partner organizations in managing internship programs.